Development of a novel diagnostic kit candidate to detect dengue antibody, using IgY and protein a positive Staphylococcus aureus - Noneng Nawangsih, Eka; Siti Halimah, Lia; Reni Yuslianti, Euis; Putu Yuni Paryati, Sayu (ACTA Medical Health Sciences, 2023)
Early diagnosis of dengue hemorrhagic fever (DHF) is very important in determining further management. Diagnostic kits are intended as relatively faster, easier, and cheaper diagnostic tools. The objectives of this experimental laboratory study was to prepare a diagnostic kit candidate to detect dengue antibody in human serum using co -agglutination methods by utilizing protein A positive Staphylococcus aureus as a carrier to bind Fc immunoglobulin fractions without altering its ability to bind antigen. To enhance the sensitivity and specificity of the diagnostic kit, chicken IgY was used as one of the components. Rabbit immunoglobulin chicken anti-IgY was used as an intermediary connection between protein A positive and Staphylococcus aureus with chicken IgY. Solution A contains Staphylococcus aureus Cowan I and rabbit immunoglobulin chicken anti-IgY serum while Solution B contains anti-dengue chicken serum and dengue antigen. The laboratory experiments produced a formula of A: B = 1~3: 1~3 (v/v), which was then tested to human serum and compared with IgM and IgG ELISA tests as the gold standard. Data on the results of the test were statistically analyzed using chi - square test. Of the 65 qualified samples used, 47.69% resulted in true positive and 41.54% resulted in true negative. Meanwhile, the remaining samples demonstrated false negative (6.15%), positive predictive value (91.2%) and negative predictive value (87.1%). The sensitivity and specificity were 89% and 90%, respectively, with no significant diffe rences (p>0.05). Therefore, co-agglutination method using S. aureus with protein A positive as a carrier can be proposed as a diagnostic kit candidate to detect human serum dengue antibody to screen dengue hemorrhagic fever cases. DOI : 10.35990/amhs.v1n3.p112-120 REFERENCES World Health Organization (WHO). Global Strategy for Dengue Prevention and Control, 2012–2020. Geneva: WHO Press; 2012. World Health Organization (WHO). Dengue and severe dengue: fact sheet; 2022. Ranjit S, Kissoon N. Dengue hemorrhagic fever and shock syndromes. Pediatr Crit Care Med. 2011;12(1):90–100. Centers for Disease Control and Prevention (CDC). Serologic test for dengue virus for healthcare provider; 2019. Pramiladevi R, Kaivalya, Kora S. Study of rapid serological tests for diagnosis of dengue. Scholars J Appl Med Sci. 2013;5:548–551. World Health Organization. Dengue hemorrhagic fever: diagnosis, treatment, prevention and control. 2nd ed. Geneva: WHO; 2009. Andries AC, Duong V, Ngan C, Ong S, Huy R, Sroin K, et al. Field evaluation and impact on clinical management of a rapid diagnostic kit that detects dengue NS1, IgM and IgG. PLoS Negl Trop Dis. 2013;6:e1993. Greenfield EA. Antibodies: A Laboratory Manual. 2nd ed. Cold Spring Harbor: Cold Spring Harbor Laboratory Press; 2012. Hanly WC, James E, Artwohl J, Bennett BT. Review of polyclonal antibody production, procedures in mammals and poultry. ILAR J. 1995;37:97–118. Castello L, Martinez BL, Heronodez K. Comparison of the agar gel precipitation, virus neutralization and enzyme-linked immunosorbent assay in the determination of antibodies to infectious bursal disease virus. Vet Mex. 1987;18:317–323. Halstead SB. Neutralization and antibody-dependent enhancement of dengue viruses. Adv Virus Res. 2003;60:421–467. doi:10.1016/S0065-3527(03)60011-4 Lardo S, Utami Y, Yohan B, Tarigan, Santoso WD, Nainggolan L, Sasmono RT. Concurrent infections of dengue virus serotypes 2 and 3 in a patient with severe dengue from Jakarta, Indonesia. Asian Pac J Trop Med. 2015;9:134–137. Silveira GF, Meyer F, Delfraro A, Mosimann ALP, Coluchi N, et al. Dengue virus type 3 isolated from a fatal case with visceral complications induces enhanced proinflammatory responses and apoptosis of human dendritic cells. J Virol. 2011;11:5374–5383. European Centre for the Validation of Alternative Methods (ECVAM). The production of avian (egg yolk) antibodies: IgY. The report and recommendation of ECVAM Workshop 21. Altern Lab Anim. 2000;24:925–934. Panbio® Dengue Duo IgM and IgG Capture ELISA. Product document. 2017. Available from: http://www.alere.com/en/home/product-details/panbio-dengue-duo-igm-and-igg-capture-elisa.html Penn State Science. Sensitivity, specificity, positive predictive value, and negative predictive value. Stat 507: Epidemiological Research Methods. 2017. Available from: https://onlinecourses.science.psu.edu/stat507/node/71 Paul WD. Fundamental Immunology. 6th ed. Philadelphia: Lippincott Williams & Wilkins; 2008. p. 174–176. Van Stralen KJ, Stel VS, Reitsma JB, Dekker FW, Zoccali C, Jager KJ. Diagnostic methods I: sensitivity, specificity, and other measures of accuracy. Kidney Int. 2009;75:1257–1263. Huang J, Doria-Rose NA, Longo NS, Laub L, Lin CL, Turk E, et al. Isolation of human monoclonal antibodies from peripheral blood B cells. Nat Protoc. 2013;8:1907–1915. Halimah LS. Study of specific polyclonal rabbit serum against chicken immunoglobulin for the development of diagnostics [Master's thesis]. Bogor: Bogor Agricultural Institute; 2001.